Pemanfaatan media pembelajaran berbasis kelas virtual di masa pandemi - Bagas Narendra Parahita; Dwi Astutik; Ghufronudin Ghufronudin; Yuhastina Yuhastina (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
During distance learning (PJJ), teachers have difficulty developing creativity regarding the online learning process, especially when compiling learning media. Service activities were carried out by the Eduscape Group Research team from the Sebelas Maret University FKIP together with the Sociology MGMP of Karanganyar Regency as an effort to optimize online learning. The learning media provided by Google for Education, especially Google Slides, was chosen to be the main target for the preparation of virtual classes because it has flexibility, ease of use, and is easily accessible by both teachers and students. The method of implementing service activities is carried out in the meeting room of SMA Negeri Karangpandan, Karanganyar Regency, face to face with stringent health protocols. Service activities consist of material presentation, demonstration, mentoring and collection of virtual class results. The result of this activity is that teachers can compose and use and create learning media through various online platforms (google slides, online quizzes, pdf converters, exploration of material content on youtube) to prepare virtual classes.